Portuguese proverbs: types and variants - Reis, Sónia (2019)
Drawing on the methodology and previous results of Rassi et al. (2014) on the automatic identification of Brazilian Portuguese proverbs, this paper reports on an extension of that experiment, but now focused on the identification of the European Portuguese proverbs and their variants. Based on a large collection of over 56 thousand Portuguese proverbs and their variants, a database of proverb types was specifically built for natural language processing, along with the finite-state tools that allow for the identification of these strings in texts. Our aim is to make these linguistic resources and language processing tools publicly available, which will undoubtedly be deemed useful assets to other paremiologic studies.